Development of a simulation model as a decision support system for sugarcane supply (2016)
This research presents a discrete-event simulation model of cane supply as a decision support system for managers in a sugarcane mill. The research considers harvesting, transporting, and unloading cane at the mill yard, including the time windows, inherent uncertainty in the system, and queues of all operations. The model was implemented in C++, and the Qt Creator development environment was used to generate a graphical interface. We found that fifty percent of the time, the trailers are waiting; we also assessed the impact of mill downtime on the unloaded cane in the mill yard. Additional environments were also evaluated: rainy period, harvesting in remote places, and an alternative configuration at the unloading area that improves the process efficiency.